Modul Penginderaan Jauh untuk Meningkatkan Kemampuan Interpretasi Citra Siswa: Penelitian - I Gede Destira Nartayana; I Putu Sriartha; I Putu Ananda Citra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study was conducted due to the low ability of senior high school students to interpret remote sensing imagery, which was caused by the lack of interactive and visual learning media. The purpose of this study was to develop an interactive flipbook -based digital learning module and to examine its validity, practicality, and effectiveness in geography learning. The research employed a Research and Development method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The results show that the developed module is highly valid based on expert validation in content, media, and language aspects. Practicality testing indicates positive responses from teachers and students. The effectiveness test shows that the module improves students’ learning outcomes significantly. Therefore, the interactive flipbook -based remote sensing module is effective for enhancing students’ image interpretation skills.